A.01 Targeted analysis of whole exome sequencing and genotype-phenotype correlation in epileptic encephalopathies. (17th June 2016) - Buerki, SE; Toyota, EB; Guella, I; McKenzie, M; Evans, D; Adam, S; van Allen, MI; Boelman, C; Horvath, G; Van Karnebeek, CD; Eydoux, P; Huh, L; et al.
Abstract : Background: Epileptic encephalopathy (EE) is a severe condition in which epileptic activity itself may contribute to severe cognitive and behavioural impairments above and beyond what might be expected from the underlying pathology alone. Next generation sequencing technologies such as whole exome sequencing (WES) can detect underlying genetic causes of in EE.Methods: This report describes genotype-phenotype correlation of 29 subjects with unexplained epileptic encephalopathy, in whom WES, targeting a list of 557 epilepsy-associated genes was performed. Epilepsy phenotyping was done according to current ILAE recommendations.Results: Median age at seizure onset was 14 months (range 1-48). Electroclinical syndromes were applicable for 16/29, 8/16 had a definite/likely diagnosis. 6/8 subjects with West syndrome had variants in ALG13, STXBP1, PAFAH1B1, SLC35A2, CDKL5 and ADSL. 2 patients with Dravet syndrome had variants in SCN1A and PCDH19 respectively. 4/29 had unspecified EE and definite/likely diagnosis due to STXBP1, POLG, and KCNQ2 (2) variants. 4/29 had a possible diagnosis involving GABRB3, ARHGEF9, PCDH19 and SCN3A variants.Conclusions: The high diagnostic yield (definite/likely diagnosis in 11/29 = 38%), involving a broad variety of epilepsy-associated genes in different electroclinical syndromes justifies the diagnostic approach of early onset EE by next generation sequencing.